Fatores relevantes na escolha de prestadores de serviços de atividades de apoio no Brasil - Paletta, Guilherme Augusto da Silva (2012)
The research aimed to explore the theme of choice of service support activities in Brazil. What are the relevant criteria that an organization must adopt to choose the service provider that contributes to the pursuit of the goals of this organization? how to choose the service provider correctly? These questions were investigated in field research. The method adopted was that of a single case study. Exploratory research was used in the logical model to interpret the evidence collected and crossed this data with little existing literature on the subject. The document analysis, direct observation of the researcher and the interviews confirmed the assumptions made. The analysis of the economic capacity of that service provider, technical skill, price and level of confidence were found in the evidence and confirmed the initial proposal as relevant factors in choosing this service provider. The research also made new discoveries that suggest future research.